Urgensi Pembentukan Lembaga Mediasi Perbankan Independen Sebagai Upaya Strategis Mewujudkan Arsitektur Perbankan - Ayu Denis Christinawati (BIP's JURNAL BISNIS PERSPEKTIF, 2021)
The business world in Indonesia is growing rapidly, marked by the number ofcommercial banks and conventional banks. This development is accompanied byvarious problems that arise from customers to banks in payment systems andservices. In this condition, the bank and the customer use mediation as analternative solution for dispute resolution between the two parties. Bankingmediation is an Indonesian Banking Architecture Program (API). This program isfocused on efforts to empower and improve banking consumer protection. Seeing the importance of the complexity of the problems above, research is compiled which is expected to be able to provide and offer solutions to encourage the creation of a healthy and strong Indonesian Banking Architecture (API) in the future. What is the basis for the urgency of establishing an independent banking mediation institution? What is a concrete solution regarding the establishment of an independent banking mediation institution by the Banking Association as a strategic effort to realize the pillars of the Indonesian Banking Architecture (API)? In this study using the Normative Juridical research method. In this context the researcher wants to study and analyze several positive legal instruments that support (support) the implementation of dispute resolution mechanisms through the mediation process in the banking business sector. Besides examining positive legal instruments to complete the analysis, it also uses supporting data in the form of banking mediation practices implemented by Bank Indonesia and several banks. The urgency of establishing a banking mediation institution in an effort to realize the Independent Banking Architecture (API) is based on two aspects, namely the economic aspect and the juridical aspect. The establishment of a banking mediation institution must be encouraged by the banking association. So that there is no access to state losses that are charged. This happened because there was a dispute settlement between the banking and the customer mediated by Bank Indonesia.